The wolf wilder - Rundell, Katherine (Simon & Schuster Books for Young Readers, 2015)
In the days before the Russian Revolution, twelve-year-old Feodora sets out to rescue her mother when the Tsar's Imperial Army imprisons her for teaching tamed wolves to fend for themselves.